Progestin and AdipoQ Receptor 3 Upregulates Fibronectin and Intercellular Adhesion Molecule-1 in Glomerular Mesangial Cells via Activating NF-κB Signaling Pathway Under High Glucose Conditions - Zou, Yezi; Chen, Zhiquan; Li, Jie; Gong, Wenyan; Zhang, Lei; Xu, Futian; Chen, Lihao; Liu, Peiqing; Huang, Heqing (Frontiers in Endocrinology, 2018)
Abstract Background: PAQR3 (Progestin and adipoQ receptor 3), is a Golgi-anchored membrane protein containing seven transmembrane helices. It has been demonstrated that PAQR3 mediates insulin resistance, glucose and lipid metabolism, and inflammation. In addition, kidney inflammatory fibrosis is an important pathological feature of diabetic nephropathy (DN). Therefore, we aimed to investigate the role of PAQR3 in diabetic kidney fibrosis as well as inflammation in DN. Object: The effect of PAQR3 on NF-B signaling pathway, expressions of fibronectin (FN) and intercellular adhesionmolecule-1 (ICAM-1) in glomerular mesangial cells (GMCs) cultured by high glucose (HG) were examined. Method: Diabetic mouse and rat models were induced by streptozotocin (STZ). GMCs were treated with HG and transfected with PAQR3 plasmids or small-interfering RNA targeting PAQR3 or NF-B. The protein levels of FN and ICAM-1 were examined by western blotting, and the transcriptional activity and DNA binding activity of NF-B were measured by dual luciferase reporter assay and electrophoretic mobility shift assay (EMSA). The interaction between PAQR3 and IKKβ (inhibitor of nuclear factor -B kinase β) was analyzed by co-immunoprecipitation. Results: PAQR3 was increased in both STZ-induced diabetic models and HG-treated GMCs. PAQR3 overexpression further increased HG-induced FN and ICAM-1 upregulation. In contrast, silencing of PAQR3 suppressed the expressions of FN and ICAM-1. PAQR3 overexpression promoted the nuclear accumulation, DNA binding activity, and transcriptional activity of NF-B. Mechanically, PAQR3 directly interacted with IKKβ. The upregulation effect of PAQR3 overexpression on the expressions of FN and ICAM-1 was abolished by the treatment of NF-B siRNA or PDTC (ammonium pyrrolidinedithiocarbamate) in HG-treated GMCs. Conclusion: PAQR3 promotes the expressions of FN and ICAM-1 via activating NF-B signaling pathway. Mechanistically, PAQR3 activates NF-B signaling pathway to mediate kidney inflammatory fibrosis through direct interaction with IKKβ in DN.